Paraquat and glyphosate resistance in Conyza bonariensis in the Western Cape in the Republic of South Africa - De Wet, Hestia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2005.